Involved-field radiotherapy for esophageal squamous cell carcinoma: theory and practice. Issue 1 (December 2016) - Li, Minghuan; Zhang, Xiaoli; Zhao, Fen; Luo, Yijun; Kong, Li; Yu, Jinming
Abstract Esophageal carcinoma (EC) is characterized by a high rate of lymph node metastasis and its spread pattern is not always predictable. Chemoradiotherapy has an important role in the treatment of EC in both the inoperable and the pre-operative settings. However, regarding the target volume for radiation, different clinical practices exist. Theoretically, in addition to the clinical target volume administered to the gross lesion, it might seem logical to deliver a certain dose to the uninvolved regional lymph node area at risk for microscopic disease. However, in practice, it is difficult because of the intolerance of normal tissue to radiotherapy (RT), particularly if all regions containing the cervical, mediastinal, and upper abdominal nodes are covered. To date, the use of elective nodal irradiation (ENI) is still controversial in the field of radiotherapy. Some investigators use involved-field radiotherapy (IFRT) in order to reduce treatment-related toxicities. It is thought that micrometastases can be controlled, to some extent, by chemotherapy and the abscopal effects of radiation. It is the presence of overtly involved lymph nodes rather than the micrometastatic nodes negatively affects survival in patients with EC. In another hand, lymph nodes stationed near primary tumors also receive considerable incidental irradiation doses that may contribute to the elimination of subclinical lesions. These data indicate that an irradiation volume covering only the gross tumor is appropriate. When using ENI or IFRT, very few patients experience solitary regional node failure and out-of-field lymph node failure is not common. Primary tumor recurrence and distant metastases, rather than regional lymph node failure, affect the overall survival in patients with EC. The available evidence indicates that the use of ENI seems to prevent or delay regional nodal relapse rather than improve survival. In a word, these data suggest that IFRT is feasible in EC patients.